Potential anti-biofilm producing marine actinomycetes isolated from sea sediments in Thailand - Leetanasaksakul, Kantinan; Thamchaipenet, Arinthip (Agriculture and Natural Resources, 2018)
Marine actinomycetes are well known as novel resources of bioactive compounds including anti-biofilm agents with various therapeutic applications. In this study, one hundred and one marine actinomycetes were isolated from sea sediments collected from Andaman sea and the Gulf of Thailand. Morphological study and partial 16S rDNA sequence analysis revealed that most of isolates belong to genus Streptomyces (n=90, 89.11%) and the rest are rare actinomycetes (n=11, 10.89%) including Actinopolymorpha, Actinomycetospora, Dietzia Nocardiopsis, Micromonospora and Mycobacterium. Among them, ten and thirteen strains significantly reduced more than 60% of biofilm formation of Escherichia coli and Staphylococcus aureus, respectively. But no such activity was found against Pseudomonas aeruginosa. Further analysis of their supernatants indicated that most of marine actinomycetes secreted non-toxic anti-biofilm agents and some accompanied with protease activity. These are preferred characteristics of anti-biofilm substances that potentially restricted biofilm forming of E. coli and S. aureus and simultaneously prevented bacteria to develop resistance.